Հայերենին տիրապետելը՝ որպես համայնքային ծառայության պաշտոն զբաղեցնելու պարտադիր պայման - Մանուկյան, Սահակ (YSU Journal of International Affairs, 2014)
The article discusses several problems concerning the knowledge of the Armenian language as an obligatory condition for occupying vacant positions of the municipal service. Studying normative legislative acts controlling above-mentioned relations it has been concluded that there are problems which impede the implementation of the equal rights of citizens to occupy the vacant position of municipal service. The article attempts to find their political and legal solutions.
Keywords: municipal service, vacant position, Armenian language, public service, equal rights, occupy the position, obligatory condition, law